Technological, economic and ecological aspects of selective coal mining from ultra-thin seams in conditions of Ukraine - Astafiev, D.; Niedbalski, Z.; Leschhorn, F.; Tymoshenko, Ye. (Розробка родовищ, 2016)
Purpose. At present one of the topical problems associated with coal seams mining is the issue of induced wall-rock coal-cutting with stone, which results in coal getting clogged with refuse stone and turning into the rock mass. All mines of Western Donbas produce coal with average ash content of 31 – 49%. Selective mining can become a solution to this problem as it allows to incorporate reserves with unconventional thickness that are in the mine balance sheet. The main objective of the present research is to substantiate selective technology of coal extraction applicability for mining of ultra thin coal seams in conditions of Ukrainian mines. Methods. Hazardous substances’ emissions into the atmosphere arising from implementation of bulk technology of coal extraction are estimated by analytical method. Findings. Consequences of the increase in power plants’ production capacity achieved by utilizing low-ash coal extracted by selective technology are presented. Originality. The research looks into economic efficiency of implementing selective extracting technology for mining reserves with unconventional thickness in Ukrainian mines, particularly in Western Donbas. Practical implications. The conducted analysis demonstrated that implementation of new technology will allow to resolve complex issues of coal quality increase, maintenance, reinforcement and reuse of mine workings, backfilling of worked-out area and improvement of ecological situation in coal mining regions.